Application of biochemical tumor markers in the diagnostics and monitoring of melanoma - Leporowska, Ewa; Kaczmarek, Aldona; Lamperska, Katarzyna; Mackiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2006)
Laboratory diagnostics plays a crucial role in oncological diagnosis of cancers especially in the first stage of tumor progression. The early detection of tumor markers (TM) in peripheral blood or tumor tissue of patients with cancer has particular significance for staging, prognosis and monitoring of the disease. TM can be defined as an antigenic protein, glycoprotein or enzyme which is produced by tumor or normal cells and is released to the blood during the neoplastic process. Melanoma shows a high metabolic activity, which is characterized by elevated synthesis of different kinds of proteins, cytokines and enzymes. Most of them are identified and utilized in clinical diagnosis procedures. Among antigens associated with melanoma progression, determination of the S100, MIA and TA90 is most valuable, both for the early detection of cancer and for the monitoring of the treatment strategy. An increase of melanine synthesis during melanoma progression generates augmentation of 5-SCD and indol derivates production, which is detectable in the blood and urine. Numerous investigations in clinical diagnosis have been focused on the evaluation of the cytokines and adhesion molecules expression in order to identify the interaction between tumor cells and host immune response. A recent investigation revealed the role of angiogenic factors in melanoma progression. Routine laboratory determination of LDH or CRP level is important for the monitoring of the treatment results. Currently, numerous investigations have been performed to find out the most specific marker for the early stage of melanoma or minimal residual disease detection and supervision. However, the unsatisfactory diagnostic sensitivity and specificity of the newly discovered candidate is the major obstacle for the regular application in the clinical practice. Usefulness of currently available diagnostic markers is limited to monitoring of the remission of the disease for the period of treatment process and detection of metastases or relapse of cancer.